ETHNOBOTANICAL STUDY OF PLANTS USED TO TREAT ASTHMA IN THE MARITIME REGION IN TOGO - Gbekley, Holaly E.; Katawa, Gnatoulma; Karou, Simplice D.; Karou, Simplice D.; Anani, Kokou; Tchadjobo, Tchacondo; Ameyapoh, Yaovi; Batawila, Komlan; Simpore, Jacques (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Asthma is one of the most common chronic diseases in modern society and it is evident that its incidenceand severity are increasing, however very little is known about the plants used in the management of the disease. Thisstudy therefore aimed to document the plants usage in the Togolese traditional medicine to treat asthma.Methodology: From January to June 2015, an ethnobotanical survey was conducted using a semi-structuredquestionnaire with traditional healers (THs) in the southern region of Togo. The importance of the plants species wasassessed by the calculated use values.Results: In Total, 121 THs (92 males and 29 females) were interviewed and 98 plants species belonging to 54 familieswere identified as curing asthma. The most represented families were: Leguminosae with 7 species followed byEuphorbiaceae and Rutaceae contributing with 6 and 5 species respectively. Based on the calculated use values themost important species were Carcica papaya L., Cataranthus roseus L., Eucalyptus camaldulensis Dehnh., Piperguineense Thonn., Eucalyptus citriodora Hook., Eucalyptus globules Labill. and Euphorbia hirta L. The leaves and theroot were the parts predominantly used to prepare the formulations, mainly decoctions, administrated by oral route.Clinical manifestations such as wheezing (91.74%), difficulty as speaking or coughing (73.55%), dyspnea (66.94%),dry cough (52.89%), sweating and increased heart rate (52.07%) were used by TH to diagnose the disease.Conclusion: This study showed initial evidence of the use of plant materials by Togolese TH to heal asthma. Theseresults could be a starting point for laboratory screenings.